2021
DOI: 10.3389/fonc.2021.695640
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Effect of Radiotherapy on Stage II/III Rectal Cancer in Different Age Groups: Formulating Radiotherapy Decision-Making Based on Age

Abstract: IntroductionTotal mesorectal excision (TME), chemotherapy (CT), and radiotherapy (RT) are usually integrated into the comprehensive treatment of stage II/III rectal cancer (RC). Neoadjuvant radiotherapy (nRT) has become the standard treatment for stage II/III RC patients to help reduce the size of a tumor or kill cancer cells that have spread. Adjuvant RT is delivered after the resection to destroy remaining cancer cells and used mainly in stage II/III RC patients who have not received preoperative radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous studies found that EORC patients were generally present with aggressive characteristics, such as elevated CEA levels, larger tumor size, advanced stages, TD, and PNI [21,22]; while, others rejected that [11]. In this study of 7951 rectal cancer patients receiving surgery directly, EORC patients had a signi cantly higher probability of pT1-2N0 stage and lower probability of positive CEA compared with their old counterparts (both P < 0.05).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies found that EORC patients were generally present with aggressive characteristics, such as elevated CEA levels, larger tumor size, advanced stages, TD, and PNI [21,22]; while, others rejected that [11]. In this study of 7951 rectal cancer patients receiving surgery directly, EORC patients had a signi cantly higher probability of pT1-2N0 stage and lower probability of positive CEA compared with their old counterparts (both P < 0.05).…”
Section: Discussionmentioning
confidence: 53%
“…In a curious paradox, younger patients are generally present with more advanced disease and worse histopathological features than their old counterparts, yet have superior or at least noninferior survival pro les[6-8]. In addition, disparate response to treatment regardless of neoadjuvant and adjuvant is reported among different age groups, although it remains controversial [9][10][11].All of the above indicate that age should be taken into consideration in the management of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that chemotherapy didn’t seem to affect the prognosis of young patients with breast cancer, which is obviously inconsistent with most studies that are not grouped by age ( 20 ). In addition, a recent study focusing on stage II/III rectal cancer revealed that radiotherapy had different effects on the survival of patients at different ages ( 21 ). Moreover, treatment methods and postoperative recurrence methods are also diverse according to the different site of primary tumor of PDAC ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of neoadjuvant radiotherapy, it is an approach using high-energy rays (such as x-rays) or particles to destroy tumor cells and it is currently used to treat rectal cancer (RC), not colon cancer [ 7 ]. In fact, it has become the standard treatment for stage II/III rectal cancer patients to help reduce the size of a tumor or kill cancer cells that have spread [ 7 ].…”
Section: Colorectal Cancer Therapeutic Challengesmentioning
confidence: 99%
“…Regarding the use of neoadjuvant radiotherapy, it is an approach using high-energy rays (such as x-rays) or particles to destroy tumor cells and it is currently used to treat rectal cancer (RC), not colon cancer [ 7 ]. In fact, it has become the standard treatment for stage II/III rectal cancer patients to help reduce the size of a tumor or kill cancer cells that have spread [ 7 ]. This treatment can also be applied after the resection to destroy remaining cancer cells and used mainly in stage II/III RC patients who have not received preoperative radiotherapy [ 7 ].…”
Section: Colorectal Cancer Therapeutic Challengesmentioning
confidence: 99%